Power systems : conversations with David Barsamian on global democratic uprisings and the new challenges to U.S. empire - Chomsky, Noam; Barsamian, David (London : Penguin, 2013)
'In this new collection of conversations, conducted from 2010 to 2012, Noam Chomsky explores the most immediate and urgent concerns: the future of democracy in the Arab world, the implications of the Fukushima nuclear disaster, the European financial crisis, the breakdown of American mainstream political institutions, and the rise of the Occupy movement. As always, Chomsky presents his ideas vividly and accessibly, with uncompromising principle and clarifying insight. The latest volume from a long-established, trusted partnership, this collection shows once again that no interlocutor engages with Chomsky more effectively than David Barsamian. These interviews will inspire a new generation of readers, as well as longtime Chomsky fans eager for his latest thinking on the many crises we now confront, both at home and abroad. They confirm that Chomsky is an unparalleled resource for anyone seeking to understand our world today'
Includes bibliographical references and index.
Keywords: Political Structure & Processes; Democratization -- Arab countries -- History -- 21st century; Arab Spring, 2010-; Occupy movement -- History -- 21st century; Protest movements -- History -- 21st century; Revolutions -- History -- 21st century